Nafkah Bagi Istri dalam Masa Iddah Talak Raj’i (Studi Pemahaman Masyarakat Kuala Baru, Aceh Singkil) - Sabaruddin Sabaruddin (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2019)
This study aims to describe the understanding of the Kuala Baru Subdistrict community about providing livelihood for raj'i iddah talak describing the divorce practices in Kuala Baru and their implications for iddah livelihood, and describing how the Kuala Baru community views the wife's livelihood during the iddah period, and explains how the legal provisions Islam towards the practice of the Kuala Baru people towards the living of the iddah in raj'i talak. This research is included in qualitative research by pointing to field research. That is research which focuses more on the results of data collection to informants who have been determined, the data sources used are primary and secondary data using qualitative data analysis. The results of the study show that divorce practices have taken place in Kuala Baru Subdistrict only through the village government, and rarely come to court. Then, the understanding of the Kuala Baru people about the giving of iddah is still very minimal, so they think that if they are divorced there are no rights and obligations of husband and wife. Therefore, based on the provisions of Islamic law the custom that occurs in the Kuala Baru community about the absence of a living iddah for a wife who is denied by raj'i is very contrary to Islamic law, even al-'urf also rejects the habits of the Kuala Baru community, and also the benefit is very detrimental to women, because their rights are not fulfilled.